If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 1 = 6 Reorder the terms: 1 + -7x = 6 Solving 1 + -7x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -7x = 6 + -1 Combine like terms: 1 + -1 = 0 0 + -7x = 6 + -1 -7x = 6 + -1 Combine like terms: 6 + -1 = 5 -7x = 5 Divide each side by '-7'. x = -0.7142857143 Simplifying x = -0.7142857143
| 8/3-2 | | 7f-8=2 | | 2x5/2+5x3/2=7x1/2 | | 7/12+1/4 | | 13/85.8 | | -c+4=-2c | | x/2+5=-12 | | -8x-2=24-9x | | 45/34a=23.3+46a | | 5.6q-3.4-4.9q=0.3q-2.3 | | 3-3(3n-3)=39 | | 3a+9b+-5a+15b= | | 5/9=h/30 | | -8x-2=24-9 | | 8+16p^2=33 | | 85.5/13 | | 9x-4=5x+4 | | 4t+5=-10+t | | v-15=9 | | 63(x-3)=9(x+3) | | 2(x+4)=3x+5 | | 7a+-9b+3a+9b= | | 5x+9=-3 | | O(5)=2(5)-1 | | 8m-7=21+m | | 12q-7=-3q+8 | | -4q=9-5q | | 20a/30+6/30=35/30 | | -5-(-15)= | | 5a^2+30a-11=0 | | -3(3-2n)=5m | | 42+2x=-30+6x |